AN EMPIRICAL STUDY ON IMPACT OF CREDIT RATING ON CREDIT RISK OF BANKS: A LITERATURE REVIEW - G, Sunitha.; Madhav, V. Venu (Indian Journal of Finance and Banking, 2021)
In the financial markets, for investors, lenders, and issuers, credit rating agencies (CRAs) have a critical part in reducing the asymmetry of information between various parties. Credit ratings allow us to recognize the credit impending of a region’s individuals. The paper clearly describes the role played in the establishment of a nation by credit rating agencies; there is a rise in new start-ups as all investors are rated favorably. Banks are helping to recognize the investment position of India. The main aim of the study is to analyze the research gap on the impact of credit rating on credit risk with a review of the literature. The study briefly explains the research gap which helps to analyze the factors which are responsible for credit risk. The study analyzes the definitions of basic terms, the origin of credit rating agencies’ objectives, and the scope of the present study and the literature review by assessing the credit rating users and examined the consequence of credit rating agencies on the Indian financial markets. Based on the nationwide and worldwide literature it is found that if the credit history of the investors is good then their credit score would be better and positive. It would also be incredibly convenient to collect loans. Finally, it is concluded that there is a positive impact of Credit Rating on Credit Risk of banking sectors in India.